The timing and direction of statutory tax rate changes by the Canadian provinces - Ferede, Ergete; Dahlby, Bev; Adjeic, Ebenezer (My University, 2013)
Tax rate changes are some of the most significant and far-reaching decisions a government can take. A good understanding of the odds of any such changes is essential for any business debating the timing and location of investments. This paper investigates the factors that affect the timing of statutory tax rate changes by Canadian provincial governments. The authors develop a simple theoretical model to explain the “stickiness” of tax rates — the factors that lead a province to decide against tinkering with the tax system — based on the presence of fixed costs of adjusting tax rates. The results indicate that if the current rate falls within a range of tax rates bracketing the optimal rate, then the government will not adjust its tax rate because the cost of the reform outweighs the potential benefits. To build up a body of evidence, this paper employs a multinomial logit model to examine the likelihood of changes to personal income tax (PIT), corporate income tax (CIT), and provincial sales tax (PST) rates by provincial governments over the period 1973-2010. Regression results indicate that provincial governments that start with higher tax rates are more likely to cut, and less likely to raise, their tax rates. A higher provincial budget deficit reduces the probability of a CIT rate cut and raises the probability of a PST rate increase. Party ideology seems to matter. Provinces with left leaning governments are less likely to cut PIT and PST rates, and more likely to raise PIT rates compared to non-left-leaning governments. The authors also find that a federal PIT rate cut raises the probability of a provincial PIT rate increase, whereas a federal CIT rate cut raises the probability of a provincial CIT rate reduction.
Keywords: optimal taxation; tax reform; tax competition